2012
DOI: 10.1021/jf301571q
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic Compositions of 50 and 30 Year Sequences of Australian Red Wines: The Impact of Wine Age

Abstract: The phenolic composition of red wine impacts upon the color and mouthfeel and thus quality of the wine. Both of these characteristics differ depending on the age of a wine, with the purple of young wines changing to brick red and the puckering or aggressive astringency softening in older wines. This study investigated the color parameters, tannin concentrations and tannin composition of a 50 year series of Cabernet Sauvignon wines from a commercial label as well as 30 year series of Cabernet Sauvignon and Shir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
71
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(80 citation statements)
references
References 43 publications
9
71
0
Order By: Relevance
“…Greater astringency intensity is directly associated with higher concen-tration and larger molecular size of tannins (Vidal et al 2003), so the reasons for the change in wine astringency with ageing have been suggested to involve a decrease in the concentration of tannins because of precipitation and a decrease in molecular size of tannins because of subunit cleavage , Chira et al 2012. Aged red wines, up to 50 years old, however, can have concentration and average molecular size of tannins similar to that of tannins of younger wines (McRae et al 2012) and yet have lower astringency. This suggests that other changes have occurred to the structure of the tannin molecules that cause the decrease in wine astringency (McRae et al 2013).…”
Section: Oxygen Exposure Barrel Treatment Bottling and Accelerated-mentioning
confidence: 99%
“…Greater astringency intensity is directly associated with higher concen-tration and larger molecular size of tannins (Vidal et al 2003), so the reasons for the change in wine astringency with ageing have been suggested to involve a decrease in the concentration of tannins because of precipitation and a decrease in molecular size of tannins because of subunit cleavage , Chira et al 2012. Aged red wines, up to 50 years old, however, can have concentration and average molecular size of tannins similar to that of tannins of younger wines (McRae et al 2012) and yet have lower astringency. This suggests that other changes have occurred to the structure of the tannin molecules that cause the decrease in wine astringency (McRae et al 2013).…”
Section: Oxygen Exposure Barrel Treatment Bottling and Accelerated-mentioning
confidence: 99%
“…Meanwhile, they are combined among themselves or with other tannins present in wine, producing larger molecules that tend to precipitate over time. Thus, the wines will become less stained, acquiring a brownish red tint 27, 26. Another study carried out by McRae et al, 27 investigated the color parameters, concentrations of tannins and anthocyanins, and tannins composition of a 50 year series of Cabernet Sauvignon wines from Australia confirmed this effect.…”
Section: Resultsmentioning
confidence: 93%
“…Thus, the wines will become less stained, acquiring a brownish red tint 27, 26. Another study carried out by McRae et al, 27 investigated the color parameters, concentrations of tannins and anthocyanins, and tannins composition of a 50 year series of Cabernet Sauvignon wines from Australia confirmed this effect. They found a concentration of anthocyanins less than 200 mg/L for wines with age of 5 years and 627 mg/L for younger wine.…”
Section: Resultsmentioning
confidence: 93%
“…Several researchers have found an elevated correlation between anthocyanins content and wine colour (Boido et al 2006, Gómez-Gallego et al 2012, McRae et al 2012). The colour-anthocyanins correlation, however, observed in our study was low for both the anthocyanins concentration measured by spectrophotometry (r < + 0.35) and for individual anthocyanins evaluated by HPLC/MS (r < +0.31).…”
Section: Llobodanin Et Al Functionality Of Young South American Red mentioning
confidence: 99%
“…A possible explanation for this divergence is that contrary to other studies, the pH of the wines was not normalised prior to the measurement of the colour in our study. Although for young red wines, the concentration of these compounds is typically quite low (Boido et al 2006, McRae et al 2012, it can account for up to 50% of their colour (Boulton 2001). As the objective of our study, however, was to evaluate commercial samples, we opted to measure the colour of the wines at their original pH, which represented the original colour, as it was presented to the consumers.…”
Section: Llobodanin Et Al Functionality Of Young South American Red mentioning
confidence: 99%